Testing the Validity of Capital Asset Pricing Model (CAPM) in the Indian Stock Market - Panwar, Vikrant (Indian Journal of Research in Capital Markets, 2016)
The capital asset pricing model (CAPM) is one of the most significant concepts in the financial investment literature which serves as a basis for the modern portfolio theories. The applicability of this model in deciding the asset prices has been rigorously tested by researchers over the years. However, the most significant studies in this regard have been conducted in context of a developed stock market and ,therefore, testing this model in context of a developing country like India may provide interesting results. The volatility in the Indian stock markets is quite high due to the under-developed financial sector. It drives a rational investor to study the applicability and effectiveness of the asset pricing models in such volatile markets. This paper aimed to test the theoretical assumptions of the CAPM in the context of the Indian stock market. This study was conducted by using data from top 30 stocks of Bombay Stock Exchange (BSE) constituting the Sensex. The results of the study indicated that in the given time frame, the CAPM is not valid in the Indian context. It also questions the robustness of CAPM and advocates for the inclusion of other factors along with beta (systematic risk) in the model, which also may have a significant impact in determining the asset prices and construction of efficient portfolios.